Architecture of intelligent credit governance system based on big data involved in panoramic fiduciary field - Wangyang LIU; Zhenqiang XIE; Qilin MU (Dianxin kexue)
In view of the existing problems and shortcomings in the current social credit management work,according to the vision and demand of the “Credible Society”,the structure of the intelligent credit governance system based on big data involved in panoramic fiduciary field was put forward,and the core theory and key technology were analyzed.Finally,three typical application scenarios were used to further illustrate the role of the architecture in social credit governance,which was of great significance to improve our government’s governance capability.